El Niño - a badly-behaved child demands attention - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
If there was a cup given for being the most-talked-about aspect of the weather, the El Niño phenomenon would win it this year. It comes at a time when climate change is being seen more and more as part of daily life